Institutionally chartered Data and Safety Monitoring Boards: structured approaches to assuring participant safety in clinical research. (1st June 2021) - Holbein, Blair; Rape, Marie T; Hammack, Barbara N; Melvin, Ann; Reider, Carson; Knox, Tamsin A
Abstract : Data and Safety Monitoring Boards (DSMBs) derived from the need to monitor large federally funded multi-center clinical trials and evolved to include commercial and other large and complex trials. Eventually, academic health centers also created institutionally focused trial monitoring mechanisms. The basic general principles that define traditional DSMBs extend to the institutional level. The primary responsibilities are assuring safety of the participants, preserving the integrity of the trial, and ensuring the reliability of the results. Institutionally chartered DSMBs meet these responsibilities but usually have fewer members, have a structure specific to the needs of the trial, are more focused and/or have different scope reviewing smaller, single site, higher risk, and investigator-initiated studies and are flexible to accommodate institution-specific requirements and approaches. Their purpose is to meet the responsibilities of oversight for safety and data integrity, ensure proper study design, rigor and conduct, as well as provide statistical support appropriate to the setting of the research. Academic health centers should recognize the importance and existence of institution level safety and data monitoring and provide support as much as possible. Investigators should have sufficient resources available to assemble DSMBs. The Clinical and Translational Science Awards Collaborative DSMB Workgroup provides an online manual to assist investigators.